URUNME: A generic software for integrated environmental modeling. (December 2020) - Lodhi, Adnan G.; Godrej, Adil N.; Sen, Dipankar; Baran, Ayden A.
Abstract: A new software application, called URUNME, was developed in C#.NET for integrated environmental modeling. URUNME provides functionality for model coupling, data storage, analysis, visualization, scenario management, and decision support systems. A graphical user interface (GUI) based on drag-and-drop flowchart type diagrams allow modelers to set-up a model application once and then focus on running and analyzing results, without needing to further address housekeeping details. Data are stored in the embedded SQLite database. Interactive dashboards can be created using multiple screens and visual elements. The built-in scenario management feature provides the capability of running multiple scenarios of a model using different input parameters, initial, and boundary conditions. This paper presents URUNME's architecture and describes how it can be utilized for creating automated integrated modeling applications by domain experts. A demonstration of capabilities is shown in a series of case studies of increasing complexity in the water and wastewater applications. Highlights: URUNME provides a one-stop solution for integrated environmental modeling. Extensive pre- and post-processing of data, analysis and visualization. Modelers can create automated model applications with scenario management. Demonstration of capabilities via case studies in water resources.